Vibrational spectra of pilocarpine hydrochloride crystals - Bento, R. R. F.; Freire, P. T. C.; Teixeira, A. M. R.; Silva, J. H.; Lima Jr., J. A.; Oliveira, M. C. F. de; Andrade Neto, M.; Romero, N. R.; Pontes, Fenelon Martinho Lima [UNESP] (Sociedade Brasileira de Física, 2009)
Pilocarpine is a natural substance with potential application in the treatment of several diseases. In this work Fourier Transform (FT)-Raman spectrum and the Fourier Transform infra red (FT-IR) spectrum of pilocarpine hydrochloride C11H17N2O2+.Cl- were investigated at 300 K. Vibrational wavenumber and wave vector have been predicted using density functional theory (B3LYP) calculations with the 6-31 G(d,p) basis set. A comparison with experiment allowed us to assign most of the normal modes of the crystal.
Keywords: Raman scattering; infrared spectroscopy; normal modes; pilocarpine hydrochloride